2015
DOI: 10.1364/boe.6.001282
|View full text |Cite
|
Sign up to set email alerts
|

Straylight, lens yellowing and aberrations of eyes in Type 1 diabetes

Abstract: Straylight, lens yellowing and ocular aberrations were assessed in a group of people with type 1 diabetes and in an age matched control group. Most of the former had low levels of neuropathy. Relative to the control group, the type 1 diabetes group demonstrated greater straylight, greater lens yellowing, and differences in some higher-order aberration co-efficients without significant increase in root-mean-square higher-order aberrations. Differences between groups did not increase significantly with age. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Straylight as a function of age in people with and without Type 1 diabetes (reproduced from Adnan et al . ).…”
Section: Straylightmentioning
confidence: 97%
See 2 more Smart Citations
“…Straylight as a function of age in people with and without Type 1 diabetes (reproduced from Adnan et al . ).…”
Section: Straylightmentioning
confidence: 97%
“…Increased straylight has been found even in people with reasonably well‐controlled diabetes [HbA 1c 62 mmol/mol (7.8%)] as compared with people without diabetes [HbA 1c 31 mmol/mol (5.0%)] (Fig. ).…”
Section: Straylightmentioning
confidence: 99%
See 1 more Smart Citation
“…1 We also considered the effects of type 1 diabetes on accommodation, 2 ocular straylight, and lens yellowing. 3 The diabetic participants in the study exhibited low levels of the classic triad of diabetes complications-neuropathy, retinopathy, and nephropathy. Differences between the diabetes group and an age-balanced control group indicated that diabetic eyes appeared as older versions of normal eyes.…”
mentioning
confidence: 98%
“…Even if they were not assessed in the present study, part of the differences between the two groups could be due to differences in higher-order aberrations. Indeed, Adnan et al 36 demonstrated that intraocular stray light, total horizontal coma, and total vertical coma were greater in subjects with type 1 diabetes mellitus than in controls. Shahidi et al 17 reported a greater amount of total high-order aberrations in subjects with diabetes than in controls.…”
Section: Discussionmentioning
confidence: 99%